2021
DOI: 10.3390/plants10091892
|View full text |Cite
|
Sign up to set email alerts
|

Fucoid Macroalgae Have Distinct Physiological Mechanisms to Face Emersion and Submersion Periods in Their Southern Limit of Distribution

Abstract: During high tide, macroalgae are submersed, facing adequate environmental conditions, however, at low tide, these species can be exposed to high UV radiation and desiccation, leading to an overproduction of reactive oxygen species, causing oxidative stress. Since intertidal organisms present differential sensitivity to abiotic fluctuations, this study aimed to evaluate the physiological responses [photosynthetic pigments, hydrogen peroxide (H2O2), lipid peroxidation (LP), and thiols and proline] of three macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…During SAW events occurring during low tide periods, Silvetia is often observed exhibiting severe drying out with fronds turning crispy. Desiccation stress is known to affect various physiological processes and conditions in rockweeds and other fucoids, including oxidative damage (Martins et al, 2021), reduced net photosynthesis, survival, and growth (Dethier et al, 2005), increased susceptibility to loss from wave action (Haring et al, 2002), and limited recruitment success (Dudgeon and Petraitis, 2001). Over time, these effects are likely to cause population declines, as observed at our monitoring sites.…”
Section: Discussionmentioning
confidence: 74%
“…During SAW events occurring during low tide periods, Silvetia is often observed exhibiting severe drying out with fronds turning crispy. Desiccation stress is known to affect various physiological processes and conditions in rockweeds and other fucoids, including oxidative damage (Martins et al, 2021), reduced net photosynthesis, survival, and growth (Dethier et al, 2005), increased susceptibility to loss from wave action (Haring et al, 2002), and limited recruitment success (Dudgeon and Petraitis, 2001). Over time, these effects are likely to cause population declines, as observed at our monitoring sites.…”
Section: Discussionmentioning
confidence: 74%
“…Considerable changes of thallus moisture make any measurements of its physiological or biochemical parameters calculated on the fresh weight (FW) basis inadequate, as it is frequently conducted for other algae or vascular plants. In our study, we calculated all the parameters per dry weight, while FW-based calculations were used in several earlier studies of intertidal seaweeds (e.g., [ 7 , 9 ]), which hampers data comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Adaptive responses of P. canaliculata to such a complicated environment are expected to require systematic rearrangements of all key physiological processes according to the phase of the tidal cycle. However, the physiological and biochemical mechanisms allowing this alga to tolerate such conditions are still largely unknown, as very few studies of intertidal seaweeds focus on Pelvetia [ 6 , 7 ]. These works and the studies of the mid and low intertidal fucoids ( Fucus vesiculosus , F. serratus , Ascophyllum nodosum ) suggest that fluctuations of physiological parameters and biochemical composition induced by the tidal cycle include changes in photosynthetic performance and pigment content [ 7 , 8 , 9 ], nutrient uptake [ 10 ], reactive oxygen species metabolism [ 7 , 11 ], osmolyte accumulation [ 1 ], and secondary metabolism [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In situ, Martins et al (2021) reported up to 60% higher chlorophyll and carotenoid contents in P. canaliculata when collected at low tide, with the xanthophyll cycle constituting an important photoprotective mechanisms in this species (De Martino et al 1997;Harker et al 1999) (see "Light"). Moreover, a de-epoxidation of the xanthophyll cycle (i.e.…”
Section: Pigmentsmentioning
confidence: 99%